Processing of Al-Si Waste Contaminated with Iron by Powder Metallurgy - Kucera, Vojtech; Dalibor, Vojtech (Manufacturing Technology Journal, 2018)
Hot dip aluminizing of steel products leads to the contamination of the batch by iron, which could significantly exceed its admissible levels. The re-processing of thus-polluted Al-Si waste by conventional casting technologies requires extensive technological adjustments, which raise the cost. Therefore, powder metallurgy was used to process Al-Si15-Fe7 alloy (in wt. %) to refine the microstructure and improved mechanical properties without further modification of chemical composition. Mechanical machining (MM) followed by spark plasma sintering (SPS) led to strong improvement of ductility, whereas mechanical machining coupled with high-energy ball milling (HEBM) and consolidation by SPS resulted in compressive strength reaching almost 1000 MPa, but with the absence of plastic deformation. In addition, both samples showed no significant change in mechanical properties even after long-term annealing at 400 °C.
Keywords: Al-Si waste; recycling; mechanical machining; high-energy ball milling; spark plasma sintering